Improving the teaching and learning quality by developing AUN-QA based course outlines - Suharmanto, Suharmanto; Hidayati, Maria; Zen, Evynurul Laily (citeus, 2013)
The primary purpose of this article is to provide a detailed process for developing AUN-QA-based course outlines as a way to improve the quality of teaching and learning. AUN-QA, which stands for ASEAN University Network Quality Assurance, is selected due to its recognized role in raising academic standards and enhancing education, research, and services among AUN member universities (AUN-QA Guideline, 2010). This study employs a research and development approach conducted through the following stages: (1) research and information collection from the AUN-QA Guideline, the current teaching and learning conditions of the English Department at State University of Malang, and existing course outline models; (2) planning the construction of questionnaire items and their distribution to students; (3) developing AUN-QA-based course outlines; (4) validating the products with AUN-QA and curriculum experts; and (5) trying out the products with students.